2023
DOI: 10.1101/2023.11.24.568563
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic reconstruction of the successful establishment of a feralized bovine population on the subantarctic island of Amsterdam

Mathieu Gautier,
Thierry Micol,
Louise Camus
et al.

Abstract: The feral cattle of the subantarctic island of Amsterdam provide an outstanding case study of a large mammalian population that was established by a handful of founders and thrived within a few generations in a seemingly inhospitable environment. Here, we investigated the genetic history and composition of this population using genotyping and sequencing data. Our inference showed an intense but brief founding bottleneck around the late 19thcentury and revealed contributions from European taurine and Indian Oce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…Nevertheless, some studies have shown evidence of genetic load purging in invasive species (Facon et al ., 2011; Tayeh et al ., 2013; Mullarkey et al ., 2013; Marchini et al ., 2016), and gene flow and/or admixture can also mask genetic load (Whiteley et al ., 2015). Furthermore, cases exist where populations, despite showing evidence of high genetic load without a clear purging signal, have successfully established and persisted in new environments (Gautier et al ., 2023; Zayed et al ., 2007). Demographic parameters and stochastic factors can influence genetic load and therefore population persistence in contrasting ways (reviewed in Robinson et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some studies have shown evidence of genetic load purging in invasive species (Facon et al ., 2011; Tayeh et al ., 2013; Mullarkey et al ., 2013; Marchini et al ., 2016), and gene flow and/or admixture can also mask genetic load (Whiteley et al ., 2015). Furthermore, cases exist where populations, despite showing evidence of high genetic load without a clear purging signal, have successfully established and persisted in new environments (Gautier et al ., 2023; Zayed et al ., 2007). Demographic parameters and stochastic factors can influence genetic load and therefore population persistence in contrasting ways (reviewed in Robinson et al .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cases exist where populations, despite showing evidence of high genetic load without a clear purging signal, have successfully established and persisted in new environments (Gautier et al, 2023;Zayed et al, 2007). Demographic parameters and stochastic factors can influence genetic load and therefore population persistence in contrasting ways (reviewed in Robinson et al (2023) and Bouzat (2010)).…”
Section: Towards a More Comprehensive Modelling Of Population Fitnessmentioning
confidence: 99%
“…Nevertheless, some studies have shown evidence of genetic load purging in invasive species (Facon et al., 2011 ; Marchini et al., 2016 ; Mullarkey et al., 2013 ; Tayeh et al., 2013 ), and gene flow and/or admixture can also mask genetic load (Whiteley et al., 2015 ). Furthermore, cases exist where populations, despite showing evidence of high genetic load without a clear purging signal, have successfully established and persisted in new environments (Gautier et al., 2023 ; Zayed et al., 2007 ). Demographic parameters and stochastic factors can influence genetic load and therefore population persistence in contrasting ways (reviewed in Robinson et al.…”
Section: Discussionmentioning
confidence: 99%
“…showing evidence of high genetic load without a clear purging signal, have successfully established and persisted in new environments (Gautier et al, 2023;Zayed et al, 2007). Demographic parameters and stochastic factors can influence genetic load and therefore population persistence in contrasting ways (reviewed in Robinson et al (2023) and Bouzat (2010)).…”
Section: Toward a More Comprehensive Modeling Of Population Fitnessmentioning
confidence: 99%